2015
DOI: 10.1080/01635581.2015.1060351
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil Enhances T Cell Function and Tumor Infiltration and Is Correlated With a Cancer Prevention Effect in HER-2/neu But Not PyMT Transgenic Mice

Abstract: Few studies have explored the effects of omega-3 polyunsaturated fatty acid (n-3 PUFA) supplementation on immune modulation in murine models of mammary carcinogenesis. HER-2/neu and PyMT mice were randomized to 2 dietary interventions: AIN-93G-based diet with 1) 11% of diet (per gram weight) as corn oil (CO) or 2) 10% of diet as menhaden fish oil plus 1% of diet as corn oil (FO). FO significantly reduced the incidence and multiplicity of tumors (P < 0.001) in HER-2/neu, but not PyMT mice. FO-fed mice had signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…It is essential to understand precisely how specific (n-3) PUFAs modulate immune function. Turbitt [38] suggested that it is possible that n-3 PUFAs induced an increase in IL-2 and IFN-g production in T cells, which may drive a Th1 response, enhance antitumor immunity, and contribute to the cancer prevention effect of n-3 PUFAs. Thus, n-3 PUFA supplementation may enhance Th1 cytokine response and may differentially alter the effector function of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to understand precisely how specific (n-3) PUFAs modulate immune function. Turbitt [38] suggested that it is possible that n-3 PUFAs induced an increase in IL-2 and IFN-g production in T cells, which may drive a Th1 response, enhance antitumor immunity, and contribute to the cancer prevention effect of n-3 PUFAs. Thus, n-3 PUFA supplementation may enhance Th1 cytokine response and may differentially alter the effector function of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Spleens were harvested and splenocytes were prepared from individual mice as described previously (22). Primary tumors were harvested during dissection, weighed, minced, and incubated with 0.03 mg/mL Liberase (Roche) and 12.5 U/mL DNase I (Sigma-Aldrich) for 45 minutes at 37 C. Following digestion, remaining pieces were mechanically disrupted, passed through a 70-mm nylon mesh strainer (BD Biosciences), layered over Lympholyte-M cell Separation Media (Cedarlane), and centrifuged at room temperature for 20 minutes at 1,200 Â g. Isolated cells were washed in cold PBS (Mediatech) and cell counts and viability were determined via Trypan Blue exclusion.…”
Section: Isolation Of Splenic and Tumor-infiltrating Immune Cellsmentioning
confidence: 99%
“…Spleens, tumor-draining lymph nodes (TDLN), and tumors were harvested, and single-cell suspensions were prepared as previously described [6,40]. Cell counts and viability were determined via trypan blue exclusion (Corning; Tewksbury, MA, USA).…”
Section: Isolation Of Spleen Lymph Node and Tumor-infiltrating Immunmentioning
confidence: 99%
“…Single cell suspensions of splenocytes, TDLN, and tumor-infiltrating immune cells were washed twice in PBS containing 0.01% bovine serum albumin at 4 • C. Cells were incubated with Fc block (Biolegend; San Diego, CA, USA) and stained with saturating concentrations of conjugated antibodies, listedin Supplemental Table S2, as previously described [6,40]. Lymphoid and myeloid cells were gated on forward vs. side scatter, and a total of 30,000 events were acquired.…”
Section: Flow Cytometric Analysesmentioning
confidence: 99%